Research for Planning 1953-64 - Planning Commission (Planning Commission Government of India, 1965)
The Research Programmes Committee Report (1953-1964) highlights the critical role of systematic research in shaping India’s post-independence socio-economic planning. Established in 1953 under the Planning Commission, the Committee coordinated studies on economic, social, political, and administrative issues of national importance. Key research areas included land reforms, agricultural management, urbanization, small-scale industries, and tenancy legislation, with a strong focus on empirical evidence to inform policy decisions. Surveys of cities such as Bombay, Delhi, Hyderabad, and Baroda provided insights into employment patterns, wages, and urban well-being, while agricultural studies assessed the impacts of land reform and farm management practices. The Committee fostered interdisciplinary collaboration between universities, research institutions, and international partners, emphasizing rigorous methodology, coordinated funding, and publication standards. Overall, the research initiatives enhanced understanding of rural-urban transitions, industrial development, and socio-economic disparities, providing policymakers with actionable data for effective planning and sustainable development strategies.
Research Programmes Committee Planning Commission Government of India
Keywords: Research Programmes Committee; Socio-Economic Research; Planning Commission; Land Reforms; Urbanization; Agricultural Management; Small-Scale Industries; Tenancy Legislation; Policy Formulation; Interdisciplinary Research; Survey Studies; Economic Development